Lung cancer in asbestos cement workers in Denmark. Issue 6 (June 1996) - Raffn, E; Villadsen, E; Engholm, G; Lynge, E
Abstract : OBJECTIVES: To study the relative and absolute risks of main types of lung cancer in a cohort of asbestos cement workers from Denmark. METHOD: A cohort of 7887 men and 576 women employed between 1928 and 1984 was compiled from the personnel files of Danish Eternit Production. The cohort was followed up for deaths, emigrations, and incident cancer cases during the period 1943-90. The observed number of lung cancer cases in the cohort was compared with the expected number based on incidences for the Danish population. Internal comparison was made with Poisson modelling. RESULTS: A total of 226 lung cancer cases were observed (223 men and three women). The standardised incidence ratio (SIR) for all lung cancer among men was 1.7 (observed number 223, expected number 129.7, 95% confidence interval (95% CI) 1.5-2.0). The SIRs were raised for all main types of lung cancer; adenocarcinoma 2.6, squamous cell carcinoma 1.7, and anaplastic carcinoma 1.5. The higher SIR for adenocarcinomas was found particularly with a latency period of 25 years or more. Among the 93 excess lung cancer cases, 36 were squamous cell carcinomas and 32 were adenocarcinomas. CONCLUSION: Asbestos cement work is associated with an increased risk of lung cancer of all main types. During the first 25 years after the start of employment this excess risk is shared almost equally between the different histological types of lung cancer, but the risk of adenocarcinomas is clearly higher after this point.